ANALYSIS OF FACTORS ASSOCIATED WITH COVERAGE OF POSTPARTUM MATERNAL VISITS IN THE WORK AREA OF THE SINGKIL COMMUNITY HEALTH CENTER, ACEH SINGKIL REGENCY IN 2020 - Khairunnisa, Nova; Sinta, Sri Ayu; Amin, Ghazali (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: Adequate monitoring and health care during pregnancy to the puerperium is very important for the survival of mother and the baby. From the record of the Singkil Health Center, the number of postpartum visits from 2017 to 2019 has decreased. The purpose of this study was to determine the analysis of the factors related to the coverage of postpartum visits in the working area of the Singkil Health Center in 2020. Method: This research is descriptive analytic using a cross sectional design. The research was conducted in the working area of the Singkil Health Center, with a total sample of 67 postpartum mothers. Data were analyzed by univariate and bivariate using the Chi Square test. Result: The results indicate that mothers with complete postpartum visits were 55.2% and those who were incomplete were 44.7%. The bivariate analysis showed that there was a relationship between knowledge (p value 0.001), attitude (p value 0.001), parity (p value 0.007), family support (p value 0.001), and the role of health workers (p value 0.003) with coverage postpartum visits. Conclusion: It is hoped that Singkil Health Center officers can increase counseling about the importance of postpartum chech-ups by health workers (midwives) during ANC 3rd trimester of ANC and postpartum through posyandu, as well as other community activities so that they can further increase knowledge, attitudes and motivation to carry out postpartum visits and accuracy schedule. so that mothers want to make a visit according to their schedule.